Allosteric targeting of the FFA2 receptor (GPR43) restores responsiveness of desensitized human neutrophils. Issue 4 (17th August 2020) - Frei, Robert; Nordlohne, Johannes; Hüser, Ulrike; Hild, Seda; Schmidt, Johannes; Eitner, Frank; Grundmann, Manuel
Abstract: The G protein-coupled free fatty acid receptor 2 (FFA2R) is highly expressed on neutrophils and was previously described to regulate neutrophil activation. Allosteric targeting of G protein-coupled receptors (GPCRs) is increasingly explored to create distinct pharmacology compared to endogenous, orthosteric ligands. The consequence of allosteric versus orthosteric FFA2R activation for neutrophil response, however, is currently largely elusive. Here, different FFA2R desensitization profiles in human neutrophils following allosteric or orthosteric activation are reported. Using a set of neutrophil functional assays to measure calcium flux, pERK1/2, chemotaxis, cellular degranulation, and oxidative burst together with holistic and pathway-unbiased whole cell sensing based on dynamic mass redistribution, it is found that the synthetic positive allosteric modulator agonist 4-CMTB potently activates neutrophils and simultaneously alters FFA2R responsiveness toward the endogenous, orthosteric agonist propionic acid (C3) after homologous and heterologous receptor desensitization. Stimulation with C3 or the hierarchically superior chemokine receptor activator IL-8 led to strong FFA2R desensitization and rendered neutrophils unresponsive toward repeated stimulation with C3. In contrast, stimulation with allosteric 4-CMTB engaged a distinct composition of signaling pathways as compared to orthosteric receptor activation and was able to activate neutrophils that underwent homologous and heterologous desensitization with C3 and IL-8, respectively. Moreover, allosteric FFA2R activation could re-sensitize FFA2 toward the endogenous agonist C3 after homologous and heterologous desensitization. Given the fact that receptor desensitization is critical in neutrophils to sense and adapt to their current environment, these findings are expected to be useful for the discovery of novel pharmacological mechanisms to modulate neutrophil responsiveness therapeutically. Graphical Abstract: The selective FFA2 receptor ago-PAM 4-CMTB re-sensitizes human neutrophils toward orthosteric FFA2 activation.